Question

( frac{cos ^{2} beta}{sin ^{2} alpha}-sin ^{2} beta frac{cos ^{2} beta}{sin ^{2} beta}-cos ^{2} beta frac{cos ^{2} alpha}{sin ^{2} alpha}+frac{sin ^{2} beta}{sin ^{2} alpha}=frac{1}{2} )
( frac{cos ^{2} beta+sin ^{2} beta}{sin ^{2} alpha}-cos ^{3} beta-cos ^{2} beta cos ^{2} alpha=1 )
( sin ^{2} alpha )
( Rightarrow quad frac{1}{sin ^{2} alpha}-cos ^{2} betaleft(1+frac{cos ^{2} alpha}{sin ^{2} alpha}right)=1 )
( Rightarrow quad frac{1}{sin ^{2} alpha}-frac{cos ^{2} beta}{sin ^{2} alpha}=1 )
( Rightarrow quad frac{1-cos ^{2} beta}{sin ^{2} alpha} Rightarrow frac{sin ^{2} beta}{sin ^{2} alpha}=1 )
( Rightarrow sin ^{2} beta=sin ^{2} alpha )
( Rightarrow beta=n pi pm alpha )
( I G ) we have to prove ( L H S=R H S / ) lie ( y ) ) then
Question is wrong -

# How 3 sinab sin? a explain this please!! For my previous sum.

Solution